Linkages Analysis for Water-carbon Nexus in Urban System. (May 2017) - Fang, Delin; Chen, Bin
Abstract: Accompanying with the blossoms of rapid urbanization, the water resource limitation and carbon emissions are two important bottlenecks for high-speed economic development. As most of the mainstay industries are correlated with water resource consumptions and carbon emissions originating from fuel combustions, the investigation of water and carbon nexus is becoming vital for the sustainable development of urban system. Linkages analysis, originating from input-output analysis, can facilitate to demonstrate the embodied flows of water and carbon inner the socio-economic system, via illustrating the backward linkage (consumer drive) and forward linkage (producer push). Accordingly, a clear map of the water-carbon nexus in urban system is drawn, detecting the major sectors and pathways associating with water consumptions and carbon emissions.